Impact of regional characteristics on firm capabilities and new product performance - Hyun, Byung-Hwan (Edelweiss Applied Science and Technology, 2025)
This study investigates the impact of various corporate capabilities on market performance among firms in Korea, with a particular focus on the disparities between those located in capital and non-capital regions. Specifically, the study examines how research and development (R&D), dynamic capability, network capability, and technology commercialization capability contribute to market performance. New product performance is incorporated as a mediating variable to better understand the pathway through which these capabilities exert their influence. In addition, dynamic capability is explored not only as a direct factor but also as a moderating variable that potentially enhances the relationship between R&D and new product performance. Methodologically, the study adopts a multi-analytical approach, utilizing importance-performance map analysis (IPMA), multigroup analysis (MGA), and fuzzy-set qualitative comparative analysis (fsQCA) to uncover key drivers and combinations of capabilities that lead to superior market outcomes across different regional contexts. The findings underscore significant regional heterogeneity, emphasizing the need for region-specific business strategies and policy interventions to enhance firm competitiveness and innovation outcomes.